Gripper with One Degree of Freedom for Prototiping of an Educational Robotic Arm - Proaño Lapuerta, Edison Andrés; Iglesias Navarro, Iván; Tobar SubiaContento, Luz María (I+ T+ C- Research, Technology and Science, 2017)
This article describes the design of a robotic “gripper” which intends to motivate and encourage students in studying science and technology. The design of the gripper must be removable and interchangeable by other models in the same robotic arm. In the first stage of the project “Design and Implementation of an Educational Robot Arm” the partial results in dynamic and didactic teaching of robotics are highlighted as the main objective. The developed clamptype prototype has the ability to lift 1kg of weight. Through programming algorithms and the usage of a force sensor, the gripper is configured to transport objects from one position to another. The results described below correspond to measurements of the first prototype that will serve as the basis for the progress and implementation of the following stages of the project